Camera‐trapping version 3.0: current constraints and future priorities for development. Issue 3 (28th January 2019) - Glover‐Kapfer, Paul; Soto‐Navarro, Carolina A.; Wearn, Oliver R.
Abstract: Camera traps are a widely used tool in wildlife research and conservation, but in situ factors such as theft, poor performance in extreme environments and damage by wildlife may be hindering the effectiveness of the technology. However, we still know little about how widespread these constraints are and which are the priorities to solve in the short‐ and mid‐term. We present results from a global survey of camera‐trappers working across a diversity of institutions and habitats, and using camera traps for a range of purposes. We show that: (1) the major current constraints on effective camera‐trapping are cost, theft and sensor performance (with 66%, 50% and 42% of respondents respectively classifying those as important or extremely important barriers for camera‐trapping); (2) the most‐needed technological developments are related to sensor performance (faster triggering responses and higher sensitivity), resistance to extreme environmental conditions (extreme temperatures and high humidity) and automated filtering of blank images; and (3) there is considerable variation among camera trap manufacturers in user‐rated performance, and none of the manufacturer ratings exhibited a trend over time, despite improvements in the technology. Our results serve as valuable market research for both open‐source and commercial camera trap developers. On the basis of our survey of camera‐trappers, we foresee a transition towards camera‐trapping 3.0 in the near‐future, consisting of both more effective camera trap units, but also greater use of wireless data transmission, sensor networks, automation of processes using algorithms and better, more collaborative tools for managing and analysing camera trap data. Ultimately, this will increase the capacity of researchers and conservationists to implement coordinated wildlife monitoring at unprecedented scales. Abstract : We present results from a global survey of camera‐trappers which show that: (1) the major current constraints on effective camera‐trapping are cost, theft and sensor performance (with 66%, 50% and 42% of respondents respectively classifying those as important or extremely important barriers for camera‐trapping); (2) the most‐needed technological developments are related to sensor performance (faster triggering responses and higher sensitivity), resistance to extreme environmental conditions (extreme temperatures and high humidity) and automated filtering of blank images; and that (3) there is considerable variation among camera trap manufacturers in user‐rated performance, and none of the manufacturer ratings exhibited a trend over time, despite improvements in the technology. Our results serve as valuable market research for both open‐source and commercial camera trap developers.